2014
DOI: 10.1002/mus.24443
|View full text |Cite
|
Sign up to set email alerts
|

C‐terminal agrin fragment is inversely related to neuromuscular fatigue in older men

Abstract: These data suggest that serum CAF concentrations were significantly related to the onset of neuromuscular fatigue independent of age and BMI in men only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…Supporting this hypothesis, some studies have shown, that CAF circulating levels are much higher in sarcopenic than in non-sarcopenic subjects (Hettwer et al, 2010;Marzetti et al, 2014a). Interestingly, recent observations highlighted an inverse correlation between circulating levels of CAF and neuromuscular fatigue obtained by the measure of vastus lateralis muscle physical work capacity threshold (Stout et al, 2015) and, in elderly patients, a link between CAF circulating levels and the loss of appendicular lean mass (Drey et al, 2013).…”
Section: Neuromuscular Junctionsmentioning
confidence: 92%
“…Supporting this hypothesis, some studies have shown, that CAF circulating levels are much higher in sarcopenic than in non-sarcopenic subjects (Hettwer et al, 2010;Marzetti et al, 2014a). Interestingly, recent observations highlighted an inverse correlation between circulating levels of CAF and neuromuscular fatigue obtained by the measure of vastus lateralis muscle physical work capacity threshold (Stout et al, 2015) and, in elderly patients, a link between CAF circulating levels and the loss of appendicular lean mass (Drey et al, 2013).…”
Section: Neuromuscular Junctionsmentioning
confidence: 92%
“…Recently, a new practical and reliable method to determine the EMG fatigue threshold has been introduced [ 60 ]. The physical working capacity at fatigue threshold (PWCFT) is defined as average of the highest power output that results in a non-significant slope coefficient for the EMG amplitude vs. time relationship and the lowest power output that results in a significant positive slope coefficient [ 61 ]. Short term exercise increases the fatigue threshold [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its activity is regulated by neurotrypsin, which cleaves it into the C-terminal agrin fragment (CAF). If there is excessive neurotrypsin activity degeneration of the neuromuscular junction and thus decreased power output ensues [ 61 ]. In a study of 22 healthy older subjects the CAF was determined from blood [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these findings (Beaver, et al, 1986;Camic, et al, 2014;Gaesser & Poole, 1996;Poole, et al, 1988Poole, et al, , 1990Ribeiro, et al, 1986) provide a physiological basis for the PWC FT model as a fatigue threshold to identify sustainable exercise intensities during treadmill running, this test has yet to be validated through constant-velocity runs to exhaustion below, at, and above the estimated PWC FT . If valid, potential uses for the PWC FT treadmill test include both the athletic performance and rehabilitative applications as during cycle ergometry (Camic, et al, 2010b;deVries, et al, 1989;Emerson, et al, 2014;Jenkins, et al, 2014;Stout, et al, 2007aStout, et al, , 2007bStout, et al, , 2015Zak, et al, 2015) that includes assessing physical fitness, evaluating the effectiveness of conditioning programs and nutritional supplements, prescribing exercise training intensities, and examining factors related to neuromuscular function in the elderly. Based on these practical applications and popularity of running, an examination into the validity of the PWC FT treadmill test is warranted.…”
Section: Introductionmentioning
confidence: 99%